Dynamic capability and competitive advantage of event management ventures in Kenya - Rebecca Chelagat Cheruon; Jacqueline Cheptepkeny Korir (Research in Hospitality Management)
Event management in the hospitality industry came into being because many corporate firms, families and friends asked hotels to organise their gatherings. For corporate firms, these events are considered training programmes, meetings, or conferences. For families, events include weddings, birthday parties, or even garden parties. When large numbers of people gather for any purpose, it requires proper management. This management of arrangements provided to people is done by the event management team. The hospitality sector includes event management. Hotel event management ensures that any event in the hotel runs smoothly. Event ventures use resources and create economic costs and benefits in equal measure. Apart from the provision of job alternatives, events raise the level of population participation in economic development, generate secondary income, enhance community stability, and are often considered to leave minimal damage to the physical environment. With rising competition in the events management industry, competitive strategies help focus on assessing organisations’ strengths, growth opportunities and competitive threats. Traditional competitive advantage models may not be applicable for smaller firms because they assume the existence of scale economies. Yet small firms cannot compete with larger organisations in economies of scale. This article therefore tries to determine the influence of dynamic capabilities on the competitive advantage of event management ventures (EMvs) in selected counties in Kenya. The sample size comprised 230 managers selected through stratified and simple random sampling techniques respectively, and 15 entrepreneurs selected using purposive sampling. The regression analysis revealed that dynamic capabilities (β = 0.295, p < 0.001) significantly influenced the competitive advantage of EMvs. The study recommends that managers should be flexible in the constantly changing environment and adapt their competencies to achieve competitive advantage.